Spondylodiscitis in Children: A Retrospective Study and Comparison With Non-vertebral Osteomyelitis - Roversi, Marco; Mirra, Gianluca; Musolino, Antonio; Barbuti, Domenico; Lancella, Laura; Deriu, Daniele; Iorio, Carlo; Villani, Alberto; Crostelli, Marco; Mazza, Osvaldo; Krzysztofiak, Andrzej (Frontiers in Pediatrics, 2021)
Objectives The aim of this study is to provide new data on pediatrics spondylodiscitis for an optimal clinical management of this site-specific osteomyelitis. Methods We reported 48 cases of pediatric spondylodiscitis and made three comparisons between: 1) tubercular and non-tubercular cases; 2) patients aged more or less than 5 years; 3) children with spondylodiscitis and 62 controls with non-vertebral osteomyelitis. Results A higher rate of sequelae was reported in patients with tubercular spondylodiscitis, but no significant differences were noted at the cut-off of 5 years of age. Compared to non-vertebral osteomyelitis, pediatric spondylodiscitis affects younger children of both genders, usually presenting with afebrile back pain, and requiring longer time to admission, hospitalization, and antibiotic therapy. Conclusions Pediatric spondylodiscitis is an insidious disease with a nonspecific presentation in childhood and peculiarities of its own. However, when clinical remission is obtained by an early start of broad-spectrum antibiotics, prolonging the therapy does not improve, nor worsens, the outcome. Surgical management is mandatory in case of vertebral instability and neurological signs but can be avoided when the infection is promptly treated with antibiotic therapy.